2023
DOI: 10.5796/electrochemistry.23-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluorine Substitution in Li<sub>3</sub>YCl<sub>6</sub> Chloride Solid Electrolytes for All-solid-state Battery

Abstract: All-solid-state batteries experience irreversible capacity loss particularly in the initial potential cycle, owing to electrolyte decomposition at the electrode/electrolyte interface. A strategy for expanding the oxidation stability of electrolytes is replace the anion in solid electrolytes with fluorine. However, fluorine substitution has a negative influence on ionic conductivity. In this study, we introduced trace amounts of fluorine replacement in Li3YCl6 solid electrolytes which exhibit high ionic conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In air batteries, the halide solid‐state electrolytes are renowned for their high potential stability, cost‐effectiveness, high ionic behavior, and scalable synthesis routes 276 . Moreover, the hygroscopic properties of these materials could be significantly decreased by depositing a protective thin layer of AlO 2 , 275 doping fluorine improves the oxidative stability of material, 10 adding additives, and composite polymer hybrid composites 115,277 . Shuting Luo tried to investigate order and disorder phase transition in Li 2 S, which would help to reduce dendrite formation.…”
Section: Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In air batteries, the halide solid‐state electrolytes are renowned for their high potential stability, cost‐effectiveness, high ionic behavior, and scalable synthesis routes 276 . Moreover, the hygroscopic properties of these materials could be significantly decreased by depositing a protective thin layer of AlO 2 , 275 doping fluorine improves the oxidative stability of material, 10 adding additives, and composite polymer hybrid composites 115,277 . Shuting Luo tried to investigate order and disorder phase transition in Li 2 S, which would help to reduce dendrite formation.…”
Section: Prospectsmentioning
confidence: 99%
“…276 Moreover, the hygroscopic properties of these materials could be significantly decreased by depositing a protective thin layer of AlO 2 , 275 doping fluorine improves the oxidative stability of material, 10 adding additives, and composite polymer hybrid composites. 115,277 Shuting Luo tried to investigate order and disorder phase transition in Li 2 S, which would help to reduce dendrite formation. Furthermore, it could be beneficial to design sulfide-based solid electrolytes in the future.…”
Section: Prospectsmentioning
confidence: 99%
“…The F-containing passivating interphases enhanced the oxidation stability of Li 3 InCl 4.8 F 1.2 to over 6 V and stabilized the cathode surfaces at high cutoff voltages while maintaining a reasonable ionic conductivity above 10 –4 S/cm . Similarly, Yamagishi et al reported that a small amount of F substitution in Li 3 YCl 6 (Li 3 YCl 5.97 F 0.03 ) improved oxidation stability without impacting ionic conductivity . In addition, Kwak et al reported fluorinated halide nanocomposite solid electrolytes ZrO 2 -2Li 2 ZrCl 5 F with high ionic conductivity and improved high-voltage stability …”
mentioning
confidence: 99%
“…Despite the promise of fluorine substitution for enhancing oxidation stability of Li 3 MCl 6 , only a few investigations on Li 3 InCl 4.8 F 1.2 , Li 3 InCl 5.6 F 0.4 , and Li 3 YCl 5.97 F 0.03 have been reported in the literature. Therefore, a thorough examination of F substitution in Li 3 MCl 6 with a diverse range of M elements and varying mixing ratios would serve as a fundamental guideline for the development of novel SE compositions. To this end, this study outlines a computationally motivated material design strategy through theoretical analyses of the phase stability, structural preference, ionic conductivity, and oxidation stability of F-substituted Li 3 MCl 6 with 18 different M 3+ elements.…”
mentioning
confidence: 99%